Effect of selective serotonin reuptake inhibitor discontinuation on anxiety-like behaviours in mice - Collins, H; Pinacho, R; Ozdemir, D; Bannerman, D; Sharp, T (SAGE Publications, 2022)
Background: Abrupt cessation of therapy with a selective serotonin reuptake inhibitor (SSRI) is associated with a discontinuation syndrome, typified by numerous disabling symptoms, including anxiety. Surprisingly, little is known of the behavioural effect of SSRI discontinuation in animals.